Optimalisasi Kemitraan Orang Tua-Sekolah dalam Penyelenggaraan Pendidikan Inklusi: Tantangan dan Strategi Implementasi di Tingkat Satuan Pendidikan - TULUS SETYA BUDI; Liftiah Liftiah; ALI FORMEN (STKIP Subang, 2026)
Inclusive education demands close collaboration between schools and parents so that children with special needs (CWSN) can optimally develop their academic and social potential. However, the implementation of parent-school partnerships at the school level still faces various challenges. This study aims to identify the main challenges and formulate implementation strategies for optimizing parent-school partnerships in the implementation of inclusive education. The research employed a qualitative approach with a case study design conducted in three elementary schools implementing inclusive education in Surabaya, Indonesia. The study involved 21 participants consisting of principals, classroom teachers, special needs teachers, and parents of CWSN. Data collection was carried out through in-depth interviews, participant observation, and document analysis. Data analysis used the Miles, Huberman, and Saldaña model. The findings revealed three main categories of challenges: structural challenges (lack of regular meeting schedules and forums), communication and understanding challenges (gaps in understanding inclusion and IEPs, one-way communication), and cultural and psychological challenges (stigma, anxiety, symbolic segregation). This study also identified five implementation strategies, including flexible regular meetings, intensive two-way communication, parental involvement in IEP development, parental empowerment through training, and the creation of an inclusive school culture. This study concludes that optimizing partnerships requires a systemic approach with the principal as the central leader. Parents are not obstacles but rather underutilized resources.